Ethiopia's financial sector and its regulation - Tony Addison; Alemayehu Geda (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2001)
Ethiopia is one of a number of SSA economies that adopted state-led development strategies in the 1970s (others include Angola and Mozambique), and suffered from intense conflict (leading to the fall of the Derg regime in 1991). The new government was therefore faced with the twin tasks of reconstructing the economy, and embarking on the transition to a market economy. As part of this process, state banks have been reorganised, the role of the private sector in the financial system has been expanded, interest-rate controls have been liberalized, and the central bank has been given new powers of financial supervision. Financial reform has been gradual, but nevertheless determined despite disagreement with the IMF over restrictions on the entry of foreign banks and the role of the largest state bank. This paper argues that gradual financial liberalization—while simultaneously investing in regulatory capacity—is the appropriate strategy for maintaining macro-economic stability and growth in Ethiopia. In this regard, the Chinese transition strategy—in which significant control was retained over the financial sector—can be a useful guide to strategy design in SSA, provided that rent-seeking can be contained.
Keywords: O10; O55; 330; sub-Saharan Africa; Ethiopia; conflict; economic reform; Bankenpolitik; Kapitalmarktliberalisierung; Äthiopien